Desenvolvimento do pensamento crítico, raciocínio clínico e tomada de decisão na formação do estudante de farmácia : diálogos, dificuldades e desafios - Silva, Adriana Oliveira dos Santos (2017)
The present study starts from the premise that the academic formation has a strong influence in the development of critical thinking, clinical reasoning and in the decision making of the student of pharmacy. The objective of the study was to highlight what has been used for the development of critical thinking, clinical reasoning and decision making in pharmacy student training. Therefore, a systematic review was carried out. The studies were extracted from the databases: LILACS, PubMed / MEDLINE, Scopus, Web of Science. The words "Thinking", "Education pharmacy", "Students, Pharmacy", "Clinical decision-making" along with their terms of entry were used as descriptors. Two reviewers independently conducted the evaluation of titles, abstracts and articles in their entirety. The evaluation of methodological quality followed the quality checklist of a BEME (Best Evidence in Medical Education) research group. Of the 11 studies included, nine reached an expected quality index. The results of these studies indicated that pharmacy students when enrolled in pre-pharmacy, PharmD and undergraduate programs in four years in the North American context, or PharmD programs based on active methodologies in the Mexican and Saudi context can significantly improve some aspects / Scores of critical thinking of pharmacy students. Although positive results have been observed, further studies are needed, as the role of academic training in the development of critical thinking, and especially in the clinical thinking and decision-making of the pharmacy student, is not yet clear. However, the literature points to the need for curricular reformulation of undergraduate courses in pharmacy, geared to its multidimensional context, since curricular were identified primarily during performance improvement in critical thinking.